An E321G MYH1 mutation is strongly associated with nonexertional rhabdomyolysis in Quarter Horses. (5th August 2018) - Valberg, Stephanie J.; Henry, Marisa L.; Perumbakkam, Sudeep; Gardner, Keri L.; Finno, Carrie J.
Abstract : Background: An E321G mutation in MYH1 was recently identified in Quarter Horses (QH) with immune‐mediated myositis (IMM) defined by a phenotype of gross muscle atrophy and myofiber lymphocytic infiltrates. Hypothesis/Objectives: We hypothesized that the MYH1 mutation also was associated with a phenotype of nonexertional rhabdomyolysis. The objective of this study was to determine the prevalence of the MYH1 mutation in QH with exertional (ER) and nonexertional (nonER) rhabdomyolysis. Animals: Quarter Horses: 72 healthy controls, 85 ER‐no atrophy, 56 ER‐atrophy, 167 nonER horses selected regardless of muscle atrophy. Methods: Clinical and histopathologic information and DNA was obtained from a database for (1) ER > 2 years of age, with or without atrophy and (2) nonER creatine kinase (CK) ≥ 5000 U/L, <5 years of age. Horses were genotyped for E321G MYH1 by pyrosequencing. Results: The MYH1 mutation was present in a similar proportion of ER‐no atrophy (1/56; 2%) and in a higher proportion of ER‐atrophy (25/85; 29%) versus controls (4/72; 5%). The MYH1 mutation was present in a significantly higher proportion of nonER (113/165; 68%) than controls either in the presence (39/42; 93%) or in absence (72/123; 59%) of gross atrophy. Lymphocytes were present in <18% of muscle samples with the MYH1 mutation. Conclusions and Clinical Importance: Although not associated with ER, the MYH1 mutation is associated with atrophy after ER. The MYH1 mutation is highly associated with nonER regardless of whether muscle atrophy or lymphocytic infiltrates are present. Genetic testing will enhance the ability to diagnose MYH1 myopathies (MYHM) in QH.